Dental and Oral Health Education Media: Effectiveness in Improving Health Students' Knowledge and Attitudes - Djannah, Sitti Nur; Trisnowati, Heni; Tukiyo, Intan Wahyuni; Solikhah, Solikhah; Sangruangake, Monthida (Universitas Ahmad Dahlan, 2025)
Background: Adolescents' dental and oral health problems are significant to pay attention to. Because the incidence rate is relatively high, adolescents/students often experience dental and oral health problems due to the lack of proper education in maintaining dental and oral hygiene and health. Through video media and pocketbooks supported by attractive visual displays and thin but informative pages, it can be one solution to providing health education to students. The purpose of this study was to determine the effectiveness of using video media and pocketbooks as educational and health promotion media for improving students' dental and oral health. Method: This study used an experimental design with a pre-test and post-test model conducted on 104 students who were taken using purposive sampling. Then, this study was analyzed using the Wilcoxon Signed-Rank test to compare the effectiveness of students' knowledge and attitudes before and after dental and oral health education. Results: The results showed increased knowledge (value: 0.000) and attitudes (value: 0.001) of students before and after being educated using pocketbook media about dental and oral health. Conclusion: providing pocketbooks and videos as health promotion education media is effective in improving students' knowledge and attitudes toward maintaining dental and oral health. Developing pocketbook content to be more varied and informative and using other promotional media to strengthen students' knowledge and attitudes is necessary.